2017
DOI: 10.18520/cs/v112/i03/569-576
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Crude Oil Using Marine <i>Bacillus species</i> from Vadinar Coast, Gujarat, India

Abstract: The marine environment is open to large sources of toxic organic waste in the form of accidental oil spills. Therefore, it is important to study microbial degradation processes that help reduce the damage caused to the environment. Universally, oil spills produce enormous public anxiety and highlight the need for costeffective, indigenous and environmentally acceptable bioremediation technologies. In recent times, advanced remedial techniques have been opted, such as solidifying, skimming, controlled burning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Research states that lipase is involved in inducing the lipolytic reactions of emulsified hydrocarbon at the lipid-water interface, thus assisting the hydrocarbon uptake [7]. Furthermore, many studies showed the presence of lipase intracellularly or extracellularly produced by hydrocarbon degraders from Bacillus and Pseudomonas species [7,9,16]. Nevertheless, in this study, lipase production does not affect the pH media (Figures 1b and 2).…”
Section: Growth and Enzyme Analysis Of Isolatesmentioning
confidence: 51%
See 1 more Smart Citation
“…Research states that lipase is involved in inducing the lipolytic reactions of emulsified hydrocarbon at the lipid-water interface, thus assisting the hydrocarbon uptake [7]. Furthermore, many studies showed the presence of lipase intracellularly or extracellularly produced by hydrocarbon degraders from Bacillus and Pseudomonas species [7,9,16]. Nevertheless, in this study, lipase production does not affect the pH media (Figures 1b and 2).…”
Section: Growth and Enzyme Analysis Of Isolatesmentioning
confidence: 51%
“…The presence of complex compounds in crude oil such as alkanes, monocyclic, and polycyclic aromatic hydrocarbons causes toxicity to the environment and human health [2,4,5]. Crude oil biodegradation has been widely studied for the past few decades [6][7][8][9]. These studies have led to numerous microorganisms and their enzymes to be isolated and characterized.…”
Section: Introductionmentioning
confidence: 99%
“…For example, research by Sorkhoh et al [15] reported that 368 genera of Bacillus isolated from oil-polluted Kuwaiti desert and two strains were capable of degrading 80-89% of crude oil (5 g/L) within 5 days at high temperature (60 °C). Recently, Mulani et al [12] have also reported that the genus Bacillus sp. which can grow efficiently on crude oil in coastal areas Vadinar, Gujarat, India, can degrade polyhydrocarbon cyclic (PHC) by 50% for 7 days.…”
Section: Introductionmentioning
confidence: 99%
“…Biosurfactants which are naturally generated by bacteria can reduce the surface tension of oil so that the crude oil will be more soluble. The more soluble crude oils can increase the accessibility of crude oils to the degrading bacteria and help them to consume hydrocarbon compounds in crude oils [12].…”
Section: Introductionmentioning
confidence: 99%
“…Due to immense utilization of petroleum based products, increased anthropogenic and industrial activities, there are irreversible and devastating effects on biodiversity as well as on human health [2]. Oil pollution is a form of pollution that leads to the release of poly aromatic hydrocarbons (PAHs) into the natural environment especially in water and soil disturbing ecosystem [3].…”
Section: Introductionmentioning
confidence: 99%